Bertolt Brecht: far beyond didactic theater (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
In this article, we analyze Bertolt Brecht's contributions to education as a process of human formation, emphasizing his method and methodology in their convergence toward reflective and transformative learning. Drawing on the concepts of epic theater and the V-effect, we discuss the possibility of a political pedagogy emerging from a pedagogical politics. It is inferred that the application of Brechtian theatrical principles to teaching and learning significantly alters the ways in which pedagogical work is understood, offering a perspective that both questions and transforms the individuals involved as well as reality itself.
Keywords: Bertolt Brecht; epic theater; V-effect; political pedagogy; pedagogical politics